Reader authority, a reading of reception theory (Journal of the College of Basic Education, 2025)
Literary criticism witnessed in its course the emergence of new critical approaches whose trends differed in terms of focusing on one of the poles of the literary work (the author, the text, the recipient) without the other two poles. The interest was in the author in light of the contextual approaches that highlighted the external factors and made them the reference and destination in the literary work. The These two trends neglected the third pole of the creative process, which is the recipient of the literary work, until the theory of reception came that focused on him (the recipient) in an attempt to clarify the fundamental role he plays in the process of constructing meaning. One of the most prominent theories in the contemporary critical arena is the theory of reception, in its German version specifically. Which broke the absolute silence regarding the marginalization that the recipient suffers, and is concerned with explaining the ways in which the letter is received by the recipient. This theory came to complete the contradictions in which structuralism occurred, as structuralism was the text, and the new thought had to create another entrance, represented by the reader and his relationship with the text, and from here was the overlap between the two approaches and the process of communication appeared, and the research presents the theory, the reader’s authority over it, the way of the relationship between them, and the aesthetics of reception theory. Reading and the extent of the theory’s impact on our living reality and its keeping pace with every place and time